Ответ:
Объяснение:
по формулам
tg(x-y)=(tgx-tgy)/(1+tgx-tgy)
tg(x+y)=(tgx+tgy)/(1-tgx-tgy)
tgп/4=1
ctgx=1/tgx
тогда
tg(п/4-a)=(tg(п/4)-tga)/(1+tg(п/4)-tga)=(1-tga)/(1+tga)
tg(п/4+a)=(tgx+tgy)/(1-tgx-tgy)=(1+tga)/(1-tga)
ctg(п/4+a)=1/tg(п/4+a)=1/((1+tga)/(1-tga))=(1-tga)/(1+tga)=tg(п/4-a)
⇒
ctg(п/4+a)=tg(п/4-a)
Автор:
andregarzatg(п/4-α)=ctg(п/4+α)
Используя формулу приведения tg(π/2-β)=ctgβ , получим
при β=π/4+α tg(π/2-β)=tg(π/2-(π/4+α))=tg(π/2-π/4+α))=tg(π/4-α)
ctgβ=ctg(п/4+α)⇒tg(п/4-α)=ctg(п/4+α). Тождество доказано.
Автор:
lexusДобавить свой ответ
Предмет:
Английский языкАвтор:
shnookiea0ajОтветов:
Смотреть
Предмет:
Английский языкАвтор:
lindsayblairОтветов:
Смотреть
Предмет:
ФизикаАвтор:
boo bugr5ozОтветов:
Смотреть
Предмет:
ХимияАвтор:
cannolikjsmОтветов:
Смотреть